Ligand-assisted degradation of carbon tetrachloride by microscale zero-valent iron - Zhang, Xianlan; Deng, Baolin; Guo, Jing; Wang, Yang; Lan, Yeqing (Journal of Environmental Management, 2011)
Degradation of carbon tetrachloride (CT) by microscale zero-valent iron (ZVI) was investigated in batch systems with or without organic ligands (ethylenediaminetetraacetic acid (EDTA), citric acid, tartaric acid, malic acid and oxalic acid) at pHs from 3.5 to 7.5. The results demonstrated that at 25°C, the dechlorination of CT by microscale ZVI is slow in the absence of organic ligands, with a pseudo-first-order rate constant of 0.0217h at pH 3.5 and being further dropped to 0.0052h at pH 7.5. However, addition of organic ligands significantly enhanced the rates and the extents of CT removal, as indicated by the rate constant increases of 39, 31, 32, 28 and 18 times in the presence of EDTA, citric acid, tartaric acid, malic acid and oxalic acid, respectively, at pH 3.5 and 25°C. The effect of EDTA was most significant; the dechlorination of CT at an initial concentration of 20mgl increased from 16.3% (no ligands) to 89.1% (with EDTA) at the end of 8h reaction. The enhanced CT degradation in the presence of organic ligands was primarily attributed to the elimination of a surface passivation layer of Fe(III) (hydr)oxides on the microscale ZVI through chelating of organic ligands with Fe(III), which maintained the exposure of active sites on ZVI surface to CT.